URGENSI (POLITIK HUKUM) HUKUM KEWARISAN DI INDONESIA MENGACU PADA KOMPILASI HUKUM ISLAM (DIKAITKAN DENGAN UNDANG-UNDANG NO. 3 TAHUN 2006 TENTANG PERADILAN AGAMA) - Sanjaya, Umar Haris (Jurnal Yuridis, 2014)
The concequenses of inheritance is happened if the heir passed away and its leaves inheritee. Inheritance is a part of the private law context in Indonesian law which is regulate the relatisionship among people. Indonesian Prvate Law context nowday put inheritance practice into three metode first is based on Civil Code, second is based on indigeneous law, and third is Kompilasi Hukum Islam. This research is study about Islamic inheritance according to Kompilasi Hukum Islam and how far the justice implementation of it to the moslem people. The statement of justice still rise many interpretation among ulama fiqh, somehow many interpretation of fiqh intheritance is based on his personal argument until Its make the judge of Islamic court tries to make his decision according his syariah law capability. This study using descriptive methodology with juridical normative. For the conclusion, Islamci inheritance in KHI is regulated to uniform many interpretation of inheritance fiqh, but its still rise the problems of justice in implementation. Its because of many ulama fiqh has different interpretation. Thus , for the practice its depend on the judge in Islamic Court.